Determinan Faktor Profitabilitas SUB Sektor Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia - Ramadon Pratama; Shelfi Malinda; Agung Putra Raneo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine and analyze the influence of CAR, NPL, BOPO, NIM, and LDR on Return On Assets (ROA) of Conventional Banks. The sample for this research is 25 conventional banks. This research uses secondary data in the form of financial ratio data originating from the annual financial reports of Conventional Banks listed on the Indonesia Stock Exchange for 2017-2021. The data analysis technique used is Multiple Linear Regression analysis. Hypothesis testing results show that the Capital Adequacy Ratio, Non-Performing Loan and Loan to Deposit Ratio variables have a negative effect on Return On Assets. Meanwhile, Operational Costs, Operational Income and Net Interest Margin have a positive effect on Return On Assets.